STRATEGI TAHFIZH MANDIRI DI KALANGAN MAHASISWA IAIN BATUSANGKAR - Risman Bustamam; Devy Aisyah; Dapit Amril (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2020)
This study aims to uncover and analyze the strategies used by IAIN Batusangkar students in the process of memorizing the Koran independently so that they are able to achieve phenomenal results. There are quite a number of students who pursue Al-Quran tahfizh in Batusangkar IAIN, spread in almost all study programs, semesters, and faculties, with a quantity of memorization between 2 to 20 juz more. The question is, how do they go through the process of tahfizh so that they succeed? This study uses a qualitative method with an empirical phenomenological approach, involving the main partisans of 12 students/hafizh/hafizah, with the criteria of having memorization of at least 3 juz Al-Qura. Data collection is done through in-depth interviews, observation, and study of documentation. The results showed that students at IAIN Batusangkar who performed tahfizh independently, in the midst of intense lecture and social activities faced with a number of obstacles, then they used a strategy by maintaining the stability of motivation to remain high, both intrinsic and extrinsic, utilizing all existing potential, and spiritual approach, and not dependent on one method and the media.